Enhanced Signal Micro-Raman Study of SiGe Nanowires and SiGe/Si Nanowire Axial Heterojunctions Grown Using Au and Ga-Au Catalysts. Issue 1751 (10th February 2015) - Anaya, J.; Torres, A.; Jiménez, J.; Prieto, C.; Rodríguez, A.; Rodríguez, T.; Ballesteros, C.
ABSTRACT: MicroRaman spectroscopy was used for the characterization of heterostructured SiGe/Si nanowires. The NWs were grown with alloyed AuGa catalysts droplets with different Ga compositions aiming to make more abrupt heterojunctions. The heterojunctions were first characterized by TEM; then the NWs were scanned by the laser beam in order to probe the heterojunction. The capability of the MicroRaman spectroscopy for studying the heterojunction is discussed. The results show that the use of catalysts with lower Ge and Si solubility (AuGa alloys) permits to achieve more abrupt junctions.